Exploring socioeconomic differences in bedtime behaviours and sleep duration in English preschool children - Jones, C; Ball, H (Wiley, 2014)
Children's sleep is critical for optimal health and development; yet sleep duration has decreased in recent decades, and many children do not have adequate sleep. Certain sleep behaviours ('sleep hygiene') are commonly recommended, and there is some evidence that they are associated with longer nighttime sleep. Parents of 84 British 3-year-old children were interviewed about their children's sleep and completed five-night/four-day sleep diaries documenting their children's sleep, from which daily sleep duration was estimated. Diaries were validated by actigraphy in a subgroup of children. Sleep hygiene behaviours (regular bedtime, reading at bedtime, falling asleep in bed) were associated with each other, and were more common in the high socioeconomic status compared to the low socioeconomic status group. Parents' reasons for not practicing sleep hygiene included difficulty, inability or inconvenience. Sleep hygiene behaviours were associated with significantly longer child sleep at night but not over 24h. Longer daytime napping compensated for shorter nighttime sleep in children whose parents did not implement sleep hygiene behaviours. Parents may need to be advised that certain behaviours are associated with longer nighttime sleep and given practical advice on how to implement these behaviours.